Building Cultural Competence: The Lived Experience of Semester Study Abroad Students. Issue 3 (July 2017) - Cox, Lauren; Crump, Lauren; Struwing, Renee; Gillum, Deborah; Abraham, Sam
Abstract : ABSTRACT: College students who participate in semester abroad programs have diverse but positive experiences. Variables such as the educational institution attended by the students and the location of the study abroad can affect the experiences of the students. There is minimal research concerning students from Christian colleges who study abroad. The purpose of this study was to investigate the lived experiences of college students participating in a semester abroad program in a developing country. Seven college students were interviewed regarding their experiences by three senior nursing students who also participated in the study abroad program. Results indicated that major factors influencing students' experiences were related to cultural immersion, role relationships, challenges encountered, and personal growth. Students reported that relationships with people and faith in Christ were strengthened through the experience.